Optimization of calcium oxide extraction from carbide lime via acid leaching: A response surface methodology analysis - Mohamad Jamil Arif, Mansor; Wong, Kevin Pak Hieng; Siti Nor Amira, Rosli; Nur Hidayati, Othman; Mohd Hizami, Mohd Yusoff; Sumaiya, Zainal Abidin (Universiti Kebangsaan Malaysia, 2024)
Calcium oxide (CaO) is one of the inorganic compounds that is widely used in industry. CaO is typically obtained through the thermal decomposition of calcite (calcium carbonate). However, with the growing need for CaO, an eco-friendly approach has emerged that focuses on deriving calcium oxide from calcium waste, especially carbide lime. The escalation in carbide lime waste is linked to the surging demand for acetylene gas, significantly contributing to the production of this by-product. The objective of this paper is to extract CaO from carbide lime by studying the interaction of each condition affects the extraction process. By using Response Surface Methodology (RSM) and Central Composite Design (CCD) with Design Expert® software, the study aims to find the best conditions for extracting CaO from carbide lime. It focuses on factors like acid concentration, leaching temperature, and solid-to-liquid ratio as independent variables. Based on RSM results, the solid-liquid ratio (S/L ratio) has a strong effect on the purity of extracted CaO, while the acid concentration and leaching temperature have the most significant effect on the yield. The best conditions to achieve the maximum yield and purity of CaO include a 2 M acetic acid concentration, a leaching temperature of 58.32 °C, and a solid-to-liquid ratio of 9.72 g/100 mL. Based on the optimum condition of the experiment, it has resulted in a yield of 64.20% and a purity of 98.63%.